Short-Lived Interfaces in Energy Materials - Borgschulte, Andreas; Terreni, Jasmin; Fumey, Benjamin; Sambalova, Olga; Billeter, Emanuel (Frontiers in Energy Research, 2022)
The kinetics of most chemical energy storage/conversion systems depend on the mass transport through matter, which is rate-limited by various kinetic barriers. The distinction of the barriers by static and dynamic interfaces helps in reducing their impact and therefore enhancing the overall kinetics. The concept is introduced along examples of static and dynamic interfaces in hydrogen storage, thermal energy storage in absorptive media, and electrochemical water splitting and CO2 reduction. In addition to the description of analysis methods to probe static and dynamic interfaces, the general strategy as well as concrete examples to overcome them are discussed.